Cyclic DNA codes over the ring F2[u]/u2-1) based on the deletion distance - Siap, Irfan; Abualrub, Taher; Ghrayeb, Ali (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
We study the structure of cyclic DNA codes over the ring F-2[u]/(u(2) - 1). We employ the deletion similarity distance on the set of code words. A set of generators for this type of codes is found. We also study the CG-content of these type of codes and their deletion distance. Examples of cyclic DNA codes are constructed with their CG-content and their corresponding deletion distance. (C) 2009 The Franklin Institute. Published by Elsevier Ltd. All rights reserved.
Keywords: Cyclic DNA codes; Rings; CG-content; Deletion distance; MOLECULAR COMPUTATION; DESIGN; Automation & Control Systems; Engineering; Mathematics